Estudio de competitividad para la toma de decisiones en la Ferretería Colombati, periodo 2023. - Montes Vera, Erick Javier (2025)
This study analyzes business competitiveness in the Colombati Hardware Store, located in Babahoyo, Ecuador, during the period 2023, with the aim of improving strategic decision making. The research and analysis process was carried out under the mixed approach (quantitative-qualitative), and an exploratory and descriptive design. Strengths, weaknesses, opportunities and threats were identified through a SWOT analysis, interviews and surveys applied to clients and managers. The results reveal that the company faces administrative and financial shortcomings, affecting its internal management and customer satisfaction. A lack of satisfaction evaluation, staff training and digital marketing strategies was observed, which limits its positioning and commercial growth. To improve your competitiveness, it is recommended to strengthen administrative management, implement marketing strategies, improve customer service and optimize strategic planning based on quantitative and qualitative data. With these actions, the company will be able to consolidate itself in the hardware market, increase its profitability and ensure its long-term sustainability.